Composition, Diversity and Health Status of Hard Corals in Satang Besar Island - Chong, Yi Xin (Universiti Malaysia Sarawak (UNIMAS), 2016)
Hard corals (also known as scleractinian corals) are the primary organisms depositing calcium carbonate (CaCOO which make up the structure of coral reefs. The primary aim of this study was to determine the composition, diversity and health status of hard corals in Satang Besar Island. This study was conducted as there is limited published data concerning the hard coral communities in teens of composition, abundance and overall health in Satang Besar Island. The live coral cover survey was carried out using the Point Intercept Line Transect (PILT) method and underwater photography was used to aid the ex-situ photo identification of the hard corals. A total of 32 species of hard corals from 18 genera and 9 families were identified and recorded in Satang Besar Island. The three most dominant hard coral species recorded were Ponies rus (340%). Ponies lobata (15.2%) and Alveopora sp (7.7%). The overall reef health in Satang Besar Island is 'Good' with an average live coral cover of 56.72%. The overall diversity index (H'=1.3-1.95) and dominance index (l/D8P=2.07-3.44) were moderately low whereas the evenness index (J'=0.72-0.85) was moderately high in Satang Besar Island. For comparison, the health status of the hard corals in terms of live coral cover and hard coral diversity in SBW is higher than in SBE. The overall growth and development of hard corals in Satang Besar Island may potentially be affected by sedimentation.